ОЦЕНКА ПОГРЕШНОСТИ ЭТАЛОННОЙ КОНДУКТОМЕТРИЧЕСКОЙ ЯЧЕЙКИ, ОБУСЛОВЛЕННОЙ НЕЭКВИПОТЕНЦИАЛЬНОСТЬЮ ПОВЕРХНОСТИ ЭЛЕКТРОДОВ - Глухенький, А.И.; Михаль, А.А. (Інститут електродинаміки НАН України, Київ, 2010)
The mathematical model for error estimation of the conversion of standard four-electrode conductometric cell conditional on non-equipotentiality of electrode face has been worked out. The conditions under which this error does not exceed 10 ppm have been specified. References 6, figures 5.